Homogenous protein programming in the mammalian left and right ventricle free walls - Phillips, Darci (American Physiological Society, 2011)
Despite identical cardiac outputs, the right (RV) and left ventricle (LV) have very different embryological origins and resting workload. These differences suggest that the ventricles have different protein programming with regard to energy metabolism and contractile elements. The objective of this study was to determine the relative RV and LV protein expression levels, with an emphasis on energy metabolism. The RV and LV protein contents of the rabbit and porcine heart were determined with quantitative gel electrophoresis (2D-DIGE), mass spectrometry, and optical spectroscopy techniques. Surprisingly, the expression levels for more than 600 RV and LV proteins detected were similar. This included proteins many different compartments and metabolic pathways. In addition, no isoelectric shifts were detected in 2D-DIGE consistent with no differential posttranslational modifications in these proteins. Analysis of the RV and LV metabolic response to work revealed that the metabolic rate increases much faster with workload in the RV compared with LV. This implies that the generally lower metabolic stress of the RV actually approaches LV metabolic stress at maximum workloads. Thus, identical levels of energy conversion and mechanical elements in the RV and LV may be driven by the performance requirements at maximum workloads. In summary, the ventricles of the heart manage the differences in overall workload by modifying the amounts of cytosol, not its composition. The constant myocyte composition in the LV and RV implies that the ratio of energy metabolism and contractile elements may be optimal for the sustained cardiac contractile activity in the mammalian heart.